Improvement in the accuracy of the dynamic behaviour prediction of a bolted structure using a simplified finite element model and model updating. Issue 1 (January 2021) - Omar, R; Rani, M N A; Yunus, M A; Rusli, M; Shah, M A S A; Izhan, W I; Mirza, W I
Abstract: Bolted joints in assembled structures contribute to the dynamic behaviour of the structures but also increase uncertainties in modelling and prediction of the dynamic behaviour. This paper presents a modelling scheme able to reduce uncertainties and increase the accuracy of the prediction. A finite element (FE) model of a bolted joint structure was developed using CBUSH, CBEAM and 3D elements representing the bolts, contacting interfaces, and structural components, respectively. Normal modes analysis was performed on the FE model to calculate the natural frequencies and mode shapes. Sensitivity analysis was formulated and used in identifying the highly sensitive design parameters of the FE model. Model updating was adopted in correlating the FE model with experimental modal analysis (EMA) and producing an updated FE model. It was found that the updated FE model is capable of predicting the dynamic behaviour of the bolted joint structure with 95 per cent accuracy. This proposed scheme demonstrated potential for applicability to the dynamic behaviour analysis of complex bolted structures.